Music education students' perceptions on effective teaching methods / Joyce None - None, Joyce (2014)
This study was conducted in order to investigate Music Education Students' Perceptions on Effective Teaching Methods. A qualitative research was used as a research design. The population of this study was the entire UiTM Bachelor Degree students from Department of Music Education, Faculty of Music, Universiti Teknologi MARA which consists of 121 students. The purposive sampling was used in order to select the sample whereby students in their final year of studies are chosen as part of the sample. Six students were selected to be the key informants for this research. A semi structured interview which consists of open-ended questions was used as a research instrument to collect the data. A content analysis was used to analyze the data in order to get the descriptive information. The findings from this study shows that Music Education students choose Discussion method as an effective teaching method for theoretical based subjects. This method helps the student to grasp the subject much better, easy to understand and help them during the revision for examination and test. Other than that, the students also had suggested a few methods that can help the lecturer during the teaching and learning in the classroom.